Mass spectrometry imaging reveals local metabolic changes in skeletal muscle due to chronic training. Issue 6 (14th March 2022) - Goto-Inoue, Naoko; Morisasa, Mizuki; Kimura, Keisuke; Mori, Tsukasa; Furuichi, Yasuro; Manabe, Yasuko; Fujii, Nobuharu L
ABSTRACT: Muscle atrophy is a major health problem that needs effective prevention and treatment approaches. Chronic exercise, an effective treatment strategy for atrophy, promotes muscle hypertrophy, which leads to dynamic metabolic changes; however, the metabolic changes vary among myofiber types. To investigate local metabolic changes due to chronic exercise, we utilized comprehensive proteome and mass spectrometry (MS) imaging analyses. Our training model exhibited hypertrophic features only in glycolytic myofibers. The proteome analyses demonstrated that exercise promoted anabolic pathways, such as protein synthesis, and significant changes in lipid metabolism, but not in glucose metabolism. Furthermore, the fundamental energy sources, glycogen, neutral lipids, and ATP, were sensitive to exercise, and the changes in these sources differed between glycolytic and oxidative myofibers. MS imaging revealed that the lipid composition differs among myofibers; arachidonic acid might be an effective target for promoting lipid metabolism during muscle hypertrophy in oxidative myofibers. Graphical Abstract: